Design and implementation of a portable, large-scale wind tunnel for wildfire research. (July 2022) - Di Cristina, Giovanni; Gallagher, Michael R.; Skowronski, Nicholas S.; Simeoni, Albert; Rangwala, Ali; Im, Seong-kyun
Abstract: Connecting the results from laboratory wildland fire experiments with in-situ field experiments under natural conditions remains an important challenge in wildland fire science, particularly because of differences in flow and boundary-layer conditions in the local atmosphere. Thus, as part of a broader investigation involving laboratory and field experimentation, a large-scale, portable wind tunnel capable of use in both the laboratory and the field was designed and implemented to bridge the two experimental domains. Two axial fans generate flow speeds of up to 8 m/s within the test section. Thorough flow-field characterization revealed good uniformity and minimal spatial variability within the flow field. Uniquely, the wind tunnel is portable; due to its modular design, the entire wind tunnel can be broken down to fit onto two shipping pallets for transportation. This portability allows for future experiments to be conducted in the field under the same boundary conditions as in the laboratory. These same boundary conditions created a unique research environment to iteratively test the effects of boundary conditions to validate computational models in different domains. The results from some of the wildland fire spread experiments conducted in the wind tunnel are presented to demonstrate and validate its laboratory capabilities. Highlights: Development of a portable wind tunnel for wildland fire research. Providing well-controlled boundary conditions for field wildfire research. Bridging scales in wildfires by multi-scale experiments. Apparatus for generating validation data for computational research.